Radiation-induced preparation of metal nanostructures in coatings of interpolyelectrolyte complexes - Klimov, Dmitry I. (2021)
Copper, silver and gold nanoparticles were obtained by reduction of metal ions under X-ray irradiation of “layer-by-layer” (LbL) coatings in a water-alcohol medium. The precursors for metal polymer composites (metallopolymer complexes) were prepared by sorption of metal ions in polyethyleneimine - poly (styrenesulfonic acid) and polyethyleneimine - poly (acrylic acid) coatings deposited on cotton fibers. EPR spectroscopy was use to characterize the complexation of metal ions in coatings with different chemical structure and variable number of polyanion-polycation layers. The effect of coating structure and thickness on the size and stability of nanoparticles was studied using TEM and microdiffraction measurements. Antibacterial activity was found for composites containing silver nanoparticles.